Analysis of Student Satisfaction Levels with Multimedia Services Sepuluh Nopember Institute of Technology (ITS) Library Using the Libqual+TM - Tondo Indra Nyata; Lolytasari Lolytasari (Alexandria: Journal of Library and Information Science, 2024)
This study aims to analyze student satisfaction with multimedia services at the Sepuluh Nopember Institute of Technology (ITS) Library using the LibQUAL+TM indicator. LibQUAL+TM is a tool developed by the Association of Research Libraries (ARL) to assess user perceptions of library service quality. The research method used is quantitative with a survey approach. The research instrument was an online questionnaire developed based on three dimensions of LibQUAL+TM: the effect of service, information control, and Library as place. Data were collected from a sample of ITS students who used the Library's multimedia services in 2023. The analysis showed that overall, students were "Satisfied" with the effect of service but "Dissatisfied" with the dimensions of information control and the Library. Gap analysis shows that student perceptions have mostly exceeded minimum expectations but are still below ideal expectations. Some aspects that need to be improved are the completeness of the multimedia collection, ease of access, and facility updates and maintenance. This research provides valuable input for ITS library managers to improve the quality of multimedia services to meet student needs and expectations.